Effect of previous history of cancer on survival of patients with a second cancer of the head and neck. Issue 5 (May 2015) - Jégu, Jérémie; Belot, Aurélien; Borel, Christian; Daubisse-Marliac, Laetitia; Trétarre, Brigitte; Ganry, Olivier; Guizard, Anne-Valérie; Bara, Simona; Troussard, Xavier; Bouvier, Véronique; Woronoff, Anne-Sophie; Colonna, Marc; et al.
Summary Objective To provide head and neck squamous cell carcinoma (HNSCC) survival estimates with respect to patient previous history of cancer. Materials and methods Data from ten French population-based cancer registries were used to establish a cohort of all male patients presenting with a HNSCC diagnosed between 1989 and 2004. Vital status was updated until December 31, 2007. The 5-year overall and net survival estimates were assessed using the Kaplan–Meier and Pohar-Perme estimators, respectively. Multivariate Cox regression models were used to assess the effect of cancer history adjusted for age and year of HNSCC diagnosis. Results Among the cases of HNSCC, 5553 were localized in the oral cavity, 3646 in the oropharynx, 3793 in the hypopharynx and 4550 in the larynx. From 11.0% to 16.8% of patients presented with a previous history of cancer according to HNSCC. Overall and net survival were closely tied to the presence, or not, of a previous cancer. For example, for carcinoma of the oral cavity, the five-year overall survival was 14.0%, 5.9% and 36.7% in case of previous lung cancer, oesophagus cancer or no cancer history, respectively. Multivariate analyses showed that previous history of cancer was a prognosis factor independent of age and year of diagnosis (p < .001). Conclusion Previous history of cancer is strongly associated with survival among HNSCC patients. Survival estimates based on patients' previous history of cancer will enable clinicians to assess more precisely the prognosis of their patients with respect to this major comorbid condition.